Disseminating Evidence-Based Practices in Secondary Transition. (October 2013) - Mustian, April; Mazzotti, Valerie L.; Test, David W.
As educators move into a new era of educational reform, it becomes imperative that teachers use evidence-based instructional practices shown to be effective for students with disabilities. One area that plays a role in this process is secondary transition. The National Secondary Transition Technical Assistance Center has identified 63 evidence-based practices for teaching secondary students with disabilities. One critical component in this process is the dissemination and implementation of these practices with high fidelity. Methods for disseminating and implementing these practices with high fidelity are discussed.